THE GROWTH PERFORMANCE OF CITRUS DERIVED FROM SOMATIC EMBRYOGENESIS PLANTLET AND SCION STOCK - Devy, Nirmala Friyanti; Yenni, Yenni; Hardiyanto, Hardiyanto (Indonesian Journal of Agricultural Science, 2014)
Somatic embryogenesis (SE) of callus culture in vitro is one of citrus propagation ways for producing free virus and genetically true-to-type plantlets. To induce growing of plantlets derived from this technology, they should be grafted ex vitro onto a citrus rootstock. The research aimed to evaluate the growth performance of citrus plants cv. Siam Kintamani (Citrus nobilis L.) that used both plantlets and scions as their stocks. The research was conducted at Tlekung Research Station, Indonesian Citrus and Subtropical Fruit Research Institute from June 2011 to December 2012. The treatments were done at nursery house by grafting a plantlet and budding a scion onto an eight-month-old Japanese Citroon (JC) rootstock plant. The grafted and budded plants of one-year old were maintained at nursery house then transplanted into the field. In the field, the research was arranged in a randomized block design with three replications and used 15 plants as unit samples. The results showed that the vegetative growth of Siam Kintamani seedling derived from SE or grafted plant was faster than that of budded plant started from 10 to 12 months after treatment in the nersery house. In the field, the growth of SE grafted plant was only significantly different up to 6 months after transplanting. Plantlets produced from SE in vitro propagation can be used as a good alternative stock material for producing healthy citrus plants. Therefore, a further research is required especially on varieties used, reproductive growth and massive planlets production.